Understanding Malay Corpora: A Content Analysis of 15 Malay Corpora - Juhary, Jowati; Bakar, Erda Wati; Shamsudin, Mardziah; Alias, Asniah (JOURNAL OF ADVANCES IN LINGUISTICS, 2021)
Corpus research becomes an important area of research of late, especially in Malaysia and for the national language, Malay language. A corpus includes texts and transcriptions of speeches for variety of situations. For this short paper, the focus is on Malay language, which is the national and official language of Malaysia. The purposes of this paper are to identify features and types of Malay Corpora and to determine the needs for a military biased Malay Corpus. In so doing, as a short paper, the methodology involves only content analysis of relevant documents on the development of Malay language corpora. Preliminary findings suggest that there are at least 15 Malay corpora in existence, and that some of the features in these corpora overlap. Further, the researchers argue for the need for a Malay Corpus for Military Operations since the existing corpora do not fully cater for this type of corpus.